Depati Leadership Values from a Cultural Citizenship ‎Perspective: Evidence from Selected Kerinci Indigenous ‎Communities - Puja Rahmanu Gusmer; Fatmariza; Susi Fitria Dewi; Isnarmi Moeis (JPI: Jurnal Pustaka Indonesia, 2026)
This study examines the leadership values embodied by the Depati through a cultural citizenship perspective in selected Kerinci indigenous communities. Using a qualitative case study design, fieldwork was conducted from March to May 2026 with nine purposively selected participants: six Depati, two community members, and one academic. Data were collected through in-depth interviews, nonparticipant observations, and document analysis. The data were analyzed through inductive thematic analysis by systematically coding, comparing, and grouping interview transcripts, field notes, and documentary evidence, while cultural citizenship served as the interpretive framework. The analysis identified eight interrelated leadership values that consistently emerged across participants’ accounts and customary practices: authority, moral integrity, justice, responsibility, trustworthiness, exemplary conduct, deliberation, and legitimacy. The findings indicate that Depati leadership functions as a culturally embedded system of governance that promotes collective responsibility, participatory decision-making, ethical leadership, and social cohesion within indigenous communities. This study contributes to citizenship scholarship by demonstrating how indigenous leadership values provide a culturally grounded understanding of cultural citizenship and extend discussions of citizenship beyond formal state institutions through customary governance practices.